Through the looking glass: perspectives on an alternative to incarceration by Utah women - Cook, Ashlee (Contemporary justice review, 2024)
This study explores the research question ‘what can we learn from the narratives of formerly incarcerated women who have participated in an alternative model of justice?’ Six women were interviewed from The Other Side Academy (TOSA) in Utah. Narrative inquiry and journaling were used to document what an alternative to incarceration looked like. Each woman gave a detailed narrative about what their lives looked like before entering the program. Themes that emerged were Doing Time and Dead at the Door. Contrary to the belief that incarceration is rehabilitative the stories these women shared revealed a different outcome. This study found that viable alternatives to incarceration exist and for a small group of Utah women I discovered this to be true. Collectively these women’s shared viewpoints of TOSA exhibited what self-transformation looks like when a restorative justice framework is followed.